Climate change from the streets : how conflict and collaboration strengthen the environmental justice movement - Méndez, Michael (Michael Anthony) (Yale University Press, 2020)
An urgent and timely story of the contentious politics of incorporating environmental justice into global climate change policy Although the science of climate change is clear, policy decisions about how to respond to its effects remain contentious. Even when such decisions claim to be guided by objective knowledge, they are made and implemented through political institutions and relationships-and all the competing interests and power struggles that this implies. Michael Méndez tells a timely story of people, place, and power in the context of climate change and inequality. He explores the perspectives and influence low income people of color bring to their advocacy work on climate change. In California, activist groups have galvanized behind issues such as air pollution, poverty alleviation, and green jobs to advance equitable climate solutions at the local, state, and global levels. Arguing that environmental protection and improving public health are inextricably linked, Mendez contends that we must incorporate local knowledge, culture, and history into policymaking to fully address the global complexities of climate change and the real threats facing our local communities.